Effect of sowing date and plant distribution patterns on seed yield of some chickpea varieties - Khalil, N.A.; EL-Metwally, EL-M. A.; EI-Murshedy, W.A.; EL-Kashum, A.M (2006)
Two field experiments were conducted at Agric. Exp. St.. Fac. Agric., Cairo Univ., Giza, Egypt during 200312004 and 200412005 seasons.
Includes references.
Summary in Arabic.
1
Keywords: Chickpea -- Varieties; Chickpea -- Breeding; Chickpea -- Yields; Chickpea -- Seeds; Sowing date